Renal endogenous stem cells: a new source for regenerative medicine in preterms? - Gavino Faa; Vassilios Fanos (Hygeia Press di Corridori Marinella, 2015)
The creation of new medical approaches based on stem cells to treat chronic kidney disease (CKD) and in particular end stage renal disease (ESRD) has become imperative in recent years, due to the significant burdens of patients affected by renal failure and to the limitations of dialysis and kidney transplantation to solve the problem. The initial prospective of utilizing stem cells for regenerating the affected kidney has been at the basis of excitement and hope for all patients affected by ESRD. Unfortunately, too many challenges have halted the possibility to make such regenerative approach a reality, and the vast majority of patients with CKD and renal insufficiency experience a reduced quality of life associated with high mortality. The problem appears particularly severe when ESDR develops in childhood. Children submitted to kidney transplantation have a 95% of survival rate at 5 years, but only 66% of them survive at 20 years after renal transplant. As a result, patients transplanted in childhood will need repeated renal transplants during their life. Renal regenerative medicine might experience a major renaissance in the next years, developing new methodologies stemmed from the previous attempts. Here, we present some major points to be addressed, in order to open a debate on the potential offered by the different regenerative methodologies: • the "exogenous" approach; • the "endogenous" approach; • the "therapeutic" approach; • the "prevention" approach.   Proceedings of the 11th International Workshop on Neonatology and Satellite Meetings · Cagliari (Italy) · October 26th-31st, 2015 · From the womb to the adult Guest Editors: Vassilios Fanos (Cagliari, Italy), Michele Mussap (Genoa, Italy), Antonio Del Vecchio (Bari, Italy), Bo Sun (Shanghai, China), Dorret I. Boomsma (Amsterdam, the Netherlands), Gavino Faa (Cagliari, Italy), Antonio Giordano (Philadelphia, USA)